Autonomous expression of RTVL-H endogenous retroviruslike elements in human cells. - Wilkinson, D A (1990)
Northern (RNA) blot analysis of RNA from various human cell lines and tissues has demonstrated that elements belonging to the RTVL-H family of human endogenous retroviruslike sequences are expressed in several cell types. The highest levels of RTVL-H-related RNAs were observed in teratocarcinoma cell line NTera2D1, HeLa cells, two bladder carcinoma cell lines, and normal amniotic tissue. Expression was also observed in normal chorion and in some other cell lines. The RTVL-H transcription pattern varied among the different cell types, but several expressed a unit-length 5.6-kilobase transcript. Characterization of cDNA clones corresponding to transcripts present in NTera2D1 cells indicates that the complex transcription pattern observed in these cells is generated by the following: (i) transcription of both full-length and deleted genomic elements, which is initiated within the 5' long terminal repeat (LTR) and, in all but one case, polyadenylated in the 3' LTR; (ii) the splicing of both unit-length transcripts and transcripts from a deleted element; (iii) transcription involving solo LTR sequences; and (iv) transcription which, in one case, reads through the 3' LTR into flanking cellular sequences. Sequence data obtained from 25 cDNA clones revealed that at least 13 RTVL-H elements are expressed in NTera2D1 cells. The positions of several termination codons within the pol region are the same among nine different elements, indicating that an ancestral RTVL-H element bearing these mutations dispersed within the genome. We also found that RTVL-H expression varied among samples of amnion and chorion tissue isolated from different individuals. These findings demonstrate that regulated autonomous expression of RTVL-H sequences occurs in human cells.